Effectiveness of Open Kinematic Chain Exercises and Closed Kinematic Chain Exercises in Adductor Groin Pain in Recreational Football Players - Raghavendra Sunilkumar Pandey1, Trupti Yadav2, Amrutkuvar Rayjade3, Radhika Chintamani4, Apoorva Kol (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Football has been growing considerably for the past decade in India. Many young adults have taken up football as their passion. However, the grounds are underdeveloped with limited number of facilities required for a safe game. Coaching facilities are inadequate and thus fail to provide basic information about the precautions to be taken during play or the necessary steps to be taken post injury. This leads to increased risk of injuries. Groin injuries comprise of 10-18% of all football injuries. Objective: The objective of the study was to compare the effects of open and CKC exercises on groin injuries in young adults who play football for recreation. Pain Assessment, Tenderness assessment and MMT were used for assessing the individuals. Method: There were total 40 subjects who were willing participants of this study of which 3 dropped out. This was a study conducted to find the effects of open and CKC exercises on groin injuries in young adults who play football for recreation. Here we evaluated the pain using VAS and tenderness grading. Muscle strength was assessed using MMT. Result: There was a significant effect of open and CKC exercises on groin injuries. There was a reduction of pain; both on activity as well as on resistance(p=0.0065 and 0.0235) respectively. Tenderness was also less (p= 0.0130). Muscle strength did not show any significant change (p= 0.1775) Conclusion: There is a significant effect of OKC and CKC exercises being administered together rather than giving only CKC exercises on reducing pain and reducing the risk of injuries in recreational football players.